Gendered outcomes in prostitution arrests in Houston, Texas - Pfeffer, Rebecca (Crime & delinquency, 2018)
This study analyzes the law enforcement response to prostitution in Houston, Texas, between 1977 and 2010 to examine whether the traditional approach to policing prostitution disproportionately penalizes women. Data included the disposition and sentencing information for 22,916 first-time prostitution arrests in Harris County. Using bivariate and multivariate analyses, we explored gender differences in the likelihood of receiving punishment, the type(s) of punishment received, and the amount of punishment for first-time prostitution offenses. We find that women were disproportionately arrested for prostitution and that women were more likely to receive a jail sentence for involvement in prostitution than men were. In contrast, male arrestees for prostitution were more likely to receive probation sentences and/or fines. This study adds to a robust body of literature suggesting that gender impacts sentencing in the criminal justice system. Yet, it is unclear whether the role of the arrestee—as either a buyer or seller—moderates the effect of gender. This quandary demonstrates the need for more comprehensive data collection about the role of the arrestee in the commercial sexual exchange